Motivational factors in young Spanish athletes: A qualitative focus drawing from self-determination theory and achievement goal perspectives - Almagro, B. J.; Saenz-Lopez, P.; Moreno-Murcia, J. A.; Spray, C. (The Sport Psychologist, 2015)
This study qualitatively examined how athletes perceive their coach`s support for autonomy, as well as athletes` motivation, satisfaction of basic psychological needs, and the 2 × 2 achievement goal framework of young Spanish athletes. Fifteen Spanish athletes (six females and nine males) between 13 and 16 years of age were interviewed from various sporting contexts. Content analysis of the interviews revealed: the coexistence of various types of motivation for the practice of these sports by the athletes that were interviewed; the presence of integrated regulation among some of these young athletes; the importance of autonomy support and the satisfaction of basic psychological needs for motivation and athletic commitment. The results are discussed on the basis of self-determination and achievement goal theory. Strategies are proposed for improving motivation and adherence to athletic practice in young athletes